Invited examiner of PhD dissertations : Ciara O'Brien (University of Cranfield), Distant external examiner of the dissertation, Title: Predicting the Ripening Behaviour of Mango Through an Understanding of Ripening Events Advisors: Carmen Alamar, Natalia Falagan, Leon Terry - Manganaris, George A. (My University, 2026)
Invited examiner of PhD dissertations.
Keywords: Sciences